Overview of Subsurface Light Transport - Dong, Yue; Lin, Steve; Guo, Baining (Material Appearance Modeling: A Data-Coherent Approach, 2013)
This chapter provides a brief overview of light transport beneath the surface of translucent materials. Methods for computing subsurface light transport using radiative transfer models and physically-based simulation are described. Techniques for acquiring subsurface scattering properties from image appearance are then presented, including those for homogeneous and heterogeneous materials. Pointers to methods that have been developed for editing the appearance of subsurface scattering or rendering the appearance under different lighting conditions are given.